HEMODYNAMIC STABILITY WITH ETOMIDATE VS PROPOFOL AS INDUCTION AGENTS IN CORONARY ARTERY BYPASS GRAFT SURGERY - Dr. Sumeet Das; Dr. Sathya Swaroop Patnaik (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BACKGROUND Maintaining hemodynamic stability during anesthetic induction is critical in patients undergoing CABG (Coronary Artery Bypass Graft) surgery due to their compromised cardiac function. Etomidate and propofol are commonly used induction agents, but they differ significantly in their cardiovascular effects. AIM: The study aims to determine which induction agent minimises peri-induction cardiovascular fluctuations and maximises patient safety during anaesthesia induction by comparing the haemodynamic stability offered by etomidate and propofol in patients undergoing CABG surgery. MATERIALS AND METHODS: This prospective study included 100 CABG patients randomized into two groups: etomidate (0.3 mg/kg, n=50) and propofol (2 mg/kg, n=50). MAP (Mean Arterial Pressure), HR (Heart Rate), hypotension incidence, and vasopressor use were assessed at baseline and post-induction. RESULTS: Etomidate showed significantly better MAP stability at 1, 3, and 5 minutes post-induction (p < 0.001). Hypotension occurred in 6% of etomidate vs. 28% of propofol patients (p = 0.003). Vasopressors were needed in 4% vs. 22% respectively (p = 0.006). HR changes were not significant. CONCLUSION Etomidate provides superior hemodynamic stability compared to propofol and is preferred for induction in high-risk CABG patients.